A Serosurvey of Multiple Pathogens in American Black Bears (Ursus americanus) in Pennsylvania, USA Indicates a Lack of Association with Sarcoptic Mange - Niedringhaus, Kevin D. (Vet Sci, 2019)
Infectious diseases, particularly of wildlife, are intrinsically linked to human and domestic animal health. Reports of sarcoptic mange in black bears (Ursus americanus) are increasing in multiple states in the USA and while the reason is unknown, mange in other species has been associated with immunosuppression from multiple causes. Serum from bears across Pennsylvania were collected to determine the seroprevalence of five pathogens important for animal and/or human health: Canine distemper virus (CDV), canine parvovirus (CPV), canine adenovirus-1 (CAV), Toxoplasma gondii, and Trichinella sp. from bears with sarcoptic mange as well as bears that were clinically normal. Several of these pathogens, particularly canine distemper virus, are associated with immunosuppression and secondary infections in other hosts. In addition to describing the seroprevalence and relating these findings to data from other regions, statistics were performed to determine if antibodies to any of these pathogens were associated with mange in bears. The overall seroprevalence to these pathogens was as follows: CDV 7.1% (17/240), CPV 16% (15/94), CAV 6.9% (6/87), Toxoplasma gondii 64.9% (194/299), and Trichinella spiralis 3.2% (7/220). While there was no association between mange and antibodies to these pathogens, infection with one or more of these pathogens has implications for bears, other wildlife, domestic animal, and human health.